Preimplantation Genetic Testing within the Public Healthcare System in Slovenia - Volk M; Writzl K; Veble A; Jaklič H; Teran N; Prosenc B; Štimpfel M; Virant Klun I; Vrtačnik Bokal E; Ban Frangež H; Peterlin B (Balkan Journal of Medical Genetics, 2024)
Preimplantation genetic testing (PGT) is the earliest form of prenatal diagnosis that has become an established procedure for couples at risk of passing a severe genetic disease to their offspring. At UMC Ljubljana, we conducted a retrospective register-based study to present 15 years of PGT service within the public healthcare system in Slovenia. We collected the data of the PGT cycles from 2004 to 2019 and compared clinical outcomes for chromosomal and monogenic diseases using different embryo biopsy and testing approaches. In addition, we assessed the extent to which PGT has become the preferred option compared to classic prenatal diagnostics. We treated 211 couples, 110 with single gene disorder, 88 with structural chromosome rearrangement and 13 for numerical chromosome aberration. There were 375 PGT cycles with oocyte retrieval, while embryo transfer was possible in 263 cases resulting in 78 deliveries and 84 children. Altogether, the clinical pregnancy rate per embryo transfer was 31% in 2004–2016 (blastomere biopsy) and 43% in 2017–19 (blastocyst biopsy), respectively. We assessed that approximately a third of couples would opt for PGT, while the rest preferred natural conception with prenatal diagnosis. Our results show that providing a PGT service within the public healthcare system has become a considerable option in pregnancy planning for couples at risk of transmitting a severe genetic disease to their offspring. In Slovenia, approximately a third of couples would opt for PGT. Although the number of cycles is small, our clinical results are comparable to larger centres.